2019
DOI: 10.1093/milmed/usz436
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health During Naval Deployment: The Protective Role of Family Support

Abstract: Introduction Minor mental health problems among service members deployed in combat areas are relatively common, but social support is a protective factor. With the advent of digital communication, as well as more frequent family separations, a stable family support system may be more important than before. In this exploratory study, we aimed to test the relationship between perceived family support and the development of minor psychiatric symptoms during a 4-month naval counter piracy mission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…We predicted that childcare responsibilities would impose extra stress and challenge to the ophthalmic personnel during the COVID-19 pandemic based on previous research; for example, Almeida et al proposed that parenting might be substantially more stressful during a pandemic because of the additional time required for caring for children and providing social support [ 30 ]. However, other research has also reported positive effects of family interactions and support on mental health [ 39 41 ]. During the particular social context of the COVID-19 pandemic, our findings show that eyecare workers did benefit from having a greater portion of the childcare responsibilities at home, potentially due to the beneficial effect of family interactions in caring for children.…”
Section: Discussionmentioning
confidence: 99%
“…We predicted that childcare responsibilities would impose extra stress and challenge to the ophthalmic personnel during the COVID-19 pandemic based on previous research; for example, Almeida et al proposed that parenting might be substantially more stressful during a pandemic because of the additional time required for caring for children and providing social support [ 30 ]. However, other research has also reported positive effects of family interactions and support on mental health [ 39 41 ]. During the particular social context of the COVID-19 pandemic, our findings show that eyecare workers did benefit from having a greater portion of the childcare responsibilities at home, potentially due to the beneficial effect of family interactions in caring for children.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its brevity, the GHQ-12 has become one of the most used instruments for detecting psychological distress in non-clinical samples (Hankins, 2008;Tomás et al, 2017). The instrument has been translated into many different languages, including Spanish (Cuéllar-Flores et al, 2014), Portuguese (Tomás et al, 2017), German (Romppel et al, 2013), French (Salama-Younes et al, 2009), Italian (Politi et al, 1994), Dutch (Cornelius et al, 2013), Norwegian (Nordmo et al, 2020), Farsi (Namjoo et al, 2017), Japanese (Suzuki et al, 2011), Thai (Gelaye et al, 2015), and Chinese (Ye, 2009). Although most research to date has used the GHQ-12 to compute a global distress score, the structure and dimensionality of the measure is still a matter of debate.…”
Section: Dimensionality Of Ghqmentioning
confidence: 99%
“…The advantage of GHQ-12 is that it is short, can easily be scored "clinically" (symptoms present or absent) as well as levels of symptoms present (Likert-type scoring). The scale was originally designed as a screen for risk for common mental disorders (Böhnke and Croudace, 2016), but has also been used as a measure of general symptom load (Johnsen et al, 1998), Positive mental health (Hu et al, 2007) and minor psychological problems (Nordmo et al, 2020). The instrument is frequently used in screening of civilian populations in different cultures (Iheanacho et al, 2015;Endsley et al, 2017;Ju et al, 2017;Tseliou et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The direct effect of deployment on mental health symptoms is probably moderated by several factors. Besides often identified risk factors for stress-related disorders such as younger age, female gender, combat exposure, or previous traumatic experiences, social support may play an important role in military service member's mental health (Cai et al, 2017; Han et al, 2014; Luciano & McDevitt-Murphy, 2017; Nordmo, Hystad, Sanden, & Johnsen, 2020). Social support can be defined as the perceived availability of support, affection, and instrumental aid from significant social partners (LaRocca & Scogin, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Social support can be defined as the perceived availability of support, affection, and instrumental aid from significant social partners (LaRocca & Scogin, 2015). Having a perception of a good quality of social support, for example by experiencing a strong family support system, may lead to a sense of purpose and a more robust mental health during and following deployment (Nordmo et al, 2020). In comparison, if service members perceive less support from family, friends, colleagues, or even society, contact moments may diminish or act as demanding stressors, and may initiate or excite the development of mental health symptoms after returning home (Nordmo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%